2007
DOI: 10.1007/s10802-007-9112-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychiatric Disorders Among Children of Different Ethnic Origin

Abstract: The present study assesses the population prevalence of DSM-IV disorders among native and immigrant children living in low socio-economic status (SES) innercity neighborhoods in the Netherlands. In the first phase of a two-phase epidemiological design, teachers screened an ethnically diverse sample of 2041 children aged 6-10 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 33 publications
7
52
1
9
Order By: Relevance
“…Few studies outside the United States have been conducted to test for differences in the prevalence of ADHD as a function of race or ethnicity. One study in the Netherlands reported initial ethnic differences in prevalence when ADHD was defined only by symptom criteria, but these differences were not significant when full DSM-IV criteria were applied [29]. Overall, these results suggest that race or ethnic differences in prevalence may be most likely to emerge when ADHD is defined by rating scales and by symptom criteria only, but the small number of available studies underscores the critical need for additional research in this area.…”
Section: Race/ethnicitymentioning
confidence: 91%
See 1 more Smart Citation
“…Few studies outside the United States have been conducted to test for differences in the prevalence of ADHD as a function of race or ethnicity. One study in the Netherlands reported initial ethnic differences in prevalence when ADHD was defined only by symptom criteria, but these differences were not significant when full DSM-IV criteria were applied [29]. Overall, these results suggest that race or ethnic differences in prevalence may be most likely to emerge when ADHD is defined by rating scales and by symptom criteria only, but the small number of available studies underscores the critical need for additional research in this area.…”
Section: Race/ethnicitymentioning
confidence: 91%
“…Studies in Colombia [21], Germany [22], Iran [23], Australia [24], and the United States [25,26] indicated that individuals from low SES environments were 1.5-4 times more likely to meet criteria for ADHD than individuals from families with high SES. However, other studies did not find a significant relation between SES and prevalence of ADHD [12,[27][28][29] suggest that additional research is needed to test more conclusively whether low SES may be a risk factor for ADHD in at least some populations. …”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…For comparison's sake, we also recruited two groups of children from a study on the detection of ADHD among children of different ethnic origin in the Netherlands (ADEON) [28]. The aim of the ADEON project was to develop and validate a tool (diagnostic score) that could be used as a rapid initial assessment of the probability of ADHD in non-referred school age children, taking ethnicity into account.…”
Section: Methods J Study Samplementioning
confidence: 99%
“…In a representative population of children and adolescents in Germany (172, 173), 18.5% of the 3-17-year-olds scored within the clinical or borderline area (174), and 14.5% of the 7-17-year-olds had at least one specific psychological symptom associated with reduction of function (175). In a twophase epidemiological study in the Netherlands including four different ethnic groups from a population of 2041 6-10-year-olds, 11% of the children had one or more impairing psychiatric disorders, which did not differ between native Dutch and immigrant children (176). Thus, it is necessary to continue to be attentive to the psychological condition of refugee children even after many years of residence in Denmark, and to make sure that they receive the necessary support, so that possible psychological problems do not become an obstacle to, for instance, their future education and working possibilities.…”
Section: Mental Health In Young Refugeesmentioning
confidence: 95%